Machinery for potato harvesting: a state-of-the-art review - Johnson, Ciaran Miceal; Auat Cheein, Fernando (Frontiers in Plant Science, 2023)
Potatoes are the fourth most important crop for human consumption. In the 18^th century, potatoes saved the European population from starvation, and since then, it has become one of the primary crops cultivated in countries such as Spain, France, Germany, Ukraine and the United Kingdom. Potato production worldwide reached 365.7 million tonnes in 2018, 354.8 million tonnes in 2019 and 359.1 million tonnes in 2020, with production expected to grow alongside the worldwide population. However, the agricultural industry is currently suffering from urbanisation. With the next generation of farmers relocating to cities, there is a diminishing and aging agricultural workforce. Consequently, farm's urgently need innovation, particularly from a technology perspective. As a result, this work is focused on reviewing the worldwide developments on potato harvesting, with an emphasis on mechatronics, the use of intelligent systems and the opportunities that raise from applications utilising the Internet of Things (IoT). Our work covers worldwide scientific publications in the last five years, sustained by public data made available from different governments. We end our review by providing a discussion on the future trends derived from our analysis.